Analisis Pengaruh Abusive Supervision terhadap Employee Creativity dengan Sleep Deprivation, Emotional Exhaustion, dan Self Efficacy sebagai Mediator - Kennia Jasmine; Fanny Martdianty (Jurnal Manajemen dan Organisasi, 2022)
The television industry has undergone many changes and disruptions and is always required to be creative in order to survive. Creative television employees play an important role in the company's performance in the midst of unfavorable environmental conditions. This study aims to examine the effect of abusive supervision on employee creativity, sleep deprivation, emotional exhaustion, and self efficacy. Besides aiming to examine the effect between variables, this study also intends to examine the impact of related variables to employee creativity and its mediating roles were also investigated. This research employed a quantitative study with an online survey of 203 television station employees in Indonesia. The structural Equation Modeling (SEM) method was used to analyze the data. Based on the research that has been done, the results showed that abusive supervision was not proven to directly and significantly affect employee creativity, this is due to the low level of abusive supervision in the television industry. However, abusive supervision has been shown to increase sleep deprivation, emotional exhaustion, and decrease employee self efficacy. This study also found that employee creativity was strongly influenced by employee self efficacy. Lastly, the results indicated that self efficacy could act as a potential mediator between abusive supervision and employee creativity.